Multigenerational effects of whole body exposure to 2.14 GHz W‐CDMA cellular phone signals on brain function in rats. Issue 7 (4th September 2014) - Shirai, Tomoyuki; Imai, Norio; Wang, Jianqing; Takahashi, Satoru; Kawabe, Mayumi; Wake, Kanako; Kawai, Hiroki; Watanabe, So‐Ichi; Furukawa, Fumio; Fujiwara, Osamu
<x xml:space="preserve">Abstract</x> The present experimental study was carried out with rats to evaluate the effects of whole body exposure to 2.14 GHz band code division multiple access (W‐CDMA) signals for 20 h a day, over three generations. The average specific absorption rate (SAR, in unit of W/kg) for dams was designed at three levels: high (<0.24 W/kg), low (<0.08 W/kg), and 0 (sham exposure). Pregnant mothers (4 rats/group) were exposed from gestational day (GD) 7 to weaning and then their offspring (F1 generation, 4 males and 4 females/dam, respectively) were continuously exposed until 6 weeks of age. The F1 females were mated with F1 males at 11 weeks old, and then starting from GD 7, they were exposed continuously to the electromagnetic field (EMF; one half of the F1 offspring was used for mating, that is, two of each sex per dam and 8 males and 8 females/group, except for all offspring for the functional development tests). This protocol was repeated in the same manner on pregnant F2 females and F3 pups; the latter were killed at 10 weeks of age. No abnormalities were observed in the mother rats (F0, F1, and F2) and in the offspring (F1, F2, and F3) in any biological parameters, including neurobehavioral function. Thus, it was concluded that under the experimental conditions applied, multigenerational whole body exposure to 2.14 GHz W‐CDMA signals for 20 h/day did not cause any adverse effects on the F1, F2, and F3 offspring. Bioelectromagnetics. 35:497–511, 2014. © 2014 Wiley Periodicals, Inc.